Storage stability of dehydrated pancit molo - Vingno, Ma. Theresa D. (2000.)
pancit molo was prepared and dried using an oven dryer.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Pancit molo; Noodles